QUALITY OF LOHMANN BROWN CHICKEN EGGS AGE 23-27 WEEKS RECEIVED COMMERCIAL RATIONS, FEED WITHOUT AND GIVEN FERMENTED DRAGON FRUIT PEEL - I M. B. S., Mahardika; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to examine the quality of Lohmann Brown chicken eggs aget 23-27 weeks fed fermented dragon fruit peel flour, which was carried out at the Field Laboratory (Teaching Farm) Campus Fapet Bukit, Jimbaran, Badung, Bali and the Poultry Laboratory of the Faculty of Animal Husbandry, University Udayana The research was carried out using a completely randomized design (CDR) consisting of 3 treatments, namely: A (ration without fermented dragon fruit peel), B (ration with 5% dragon fruit peel), C (commercial ration), each treatment was repeated 5 time and each replication using 3 laying hens. The variables observed were: egg weight, egg shell weight, shell thickness, egg yolk color, and haugh unit. The results showed that the provision of rations with and additional 5% fermented dragon fruit peel, and commercial ration significantly increased egg weight, shell weight, shell thickness, egg yolk color, and haugh unit (P<0,05), but had no effect (P>0,05) on egg Ph. Based on the results of the study, it can be concluded that the provisionof rations with the addition of 5% fermented dragon fruit peel flour and commercial rations can increase egg weight, egg shell weight, egg shell thickness, egg yolk color, and haugh unit. Key words: Lohmann Brown chicken egg quality, fermented dragon fruit peel ration